KAJIAN YURIDIS PENGUJIAN (JUDICIAL REVIEW) UNDANG-UNDANG NO. 32 TAHUN 2002 TENTANG PENYIARAN: STUDI PUTUSAN MKRI No. 71/PU-XI/2013 - Cucuk Indratno (Jurnal Ilmu dan Budaya, 2019)
Under the Constitution of Indonesia (the Undang-Undang Dasar), the Constutional Court (the Mahkamah Konstitusi) has the authority to judge  cases brought to the Court. The decision of the Court is final and binding. This time a law of the Helath (the Undang-Undang No. 32, 2002) was submitted to the court. This Law speaks about tobacco which is addictive and there has been an affirmative action to control its existences however, how much tobacco is damaging to health, that law was rejected by the 8 members of the court. In that law (the Undang-Undang Kesehatan No. 32, 2002), it obiviously was on purpose displaying only the form of the cigarette instead.